From Authority to Justification: The Epistemological Foundations of Joseph Raz’s Legal Philosophy - Silalahi, Artha Debora; Mustansyir, Rizal; Tjahyadi, Sindung (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2025)
This article examines the intrinsic relationship between law and values through the lens of legal epistemology, focusing on Joseph Raz’s legal philosophy. It investigates how judicial interpretation, shaped by epistemological foundations, influences legal reasoning and outcomes. Central to the discussion are normative challenges in adjudication such as ambiguity, uncertainty, and moral conflict. It also discusses how Raz’s thought of legal authority and the chain of validity among norms provide a framework for evaluating the legitimacy and justification of legal decisions. Raz argues that legal authority must offer independently justified reasons for action, reinforcing the law’s role in maintaining social order. The article further examines how legal structures shape and sustain societal values, positioning legal epistemology not only as a tool for understanding the basis of authority but also as a normative foundation for aligning legal principles with societal values. In conclusion, the research affirms that a robust epistemological approach to law, as proposed by Raz, is crucial for ensuring legitimacy and fairness in legal systems, making legal epistemology indispensable in affirming the normative force of law in contemporary society.